The Partial Implantation, at 1:2 Scale, of Rabaçal's Roman Villa - João Pedro Xavier (2011)
Our aim is the implantation in the terrain of the octagonal peristyle of the Roman villa existing in Rabaçal, at scale 1:2. We will follow, as close as possible, the known Roman procedures, as described by Vitruvius and other ancient sources, and depicted in Roman sculptural reliefs.